1999
DOI: 10.1007/bf02237135
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of small-bowel obstruction and adhesiolysis after open colorectal and general surgery

Abstract: In this retrospective study of Medicare patients, we learned that bowel obstruction, adhesiolysis for obstructions, and additional abdominal surgery occurred more often after abdominal surgery than was previously published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
105
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(112 citation statements)
references
References 5 publications
3
105
0
4
Order By: Relevance
“…However, laparotomy treatment of SBO has been associated with substantial morbidities including wound infections, increased postoperative pain, prolonged ileus, and reduced postoperative pulmonary function.2 In addition, the estimated rate of obstruction recurrence is 12%~17%. 1,22,23 Since the first report of Bastug et al for successful laparoscopic adhesiolysis in 1991, 9 technological developments and increased experience with LS have led to a number of studies reporting advantages of LS, including a shorter postoperative hospital stay, fewer complications, and less postoperative pain. [10][11][12][13][14][15][16][17] Kim et al reported significant reductions in return of bowel function (4.3 vs. 6.6 days, p=0.02), and hospital stay (8.1 vs. 15.2 days, p=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…However, laparotomy treatment of SBO has been associated with substantial morbidities including wound infections, increased postoperative pain, prolonged ileus, and reduced postoperative pulmonary function.2 In addition, the estimated rate of obstruction recurrence is 12%~17%. 1,22,23 Since the first report of Bastug et al for successful laparoscopic adhesiolysis in 1991, 9 technological developments and increased experience with LS have led to a number of studies reporting advantages of LS, including a shorter postoperative hospital stay, fewer complications, and less postoperative pain. [10][11][12][13][14][15][16][17] Kim et al reported significant reductions in return of bowel function (4.3 vs. 6.6 days, p=0.02), and hospital stay (8.1 vs. 15.2 days, p=0.04).…”
Section: Discussionmentioning
confidence: 99%
“…Some asymmetry, however, is due to high incidences derived from high quality studies designed to assess incidences of small bowel obstruction or enterotomy. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] That is, some smaller low quality studies reporting lower incidences were possibly not identified. Our sensitivity analyses, however, showed that our results were quite robust, so we do not expect that these smaller low quality studies would change our results.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…Evidence shows that adhesion barriers effectively reduce adhesion formation in high risk surgery. [13][14][15][16][17][18][19][20][21][22][23][24] The detailed knowledge of the disease burden of adhesions now available may be used to power future trials of anti-adhesive barriers preventing clinically relevant outcomes of adhesions.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Adhesive SBO is a hazard especially of colon resection, affecting 15% within 2 years following surgery [3]. On the other hand, colon resection is a dominant precursor of early [4, 5]and late postoperative adhesive SBO [6, 7]in a population undergoing various abdominal procedures.…”
Section: Discussionmentioning
confidence: 99%